Cultorological Approach to Training of the Future Managers of Tourism in Precarpathia - Chorna , Marianna (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article deals with the «culturological approach» to the professional training of future managers of tourism in Precarpathia. As the Precarpathian region attracts thousands of tourists year-round the demand of training qualified specialists in the sphere of tourism and hospitality is constantly growing. Nowadays the question of a successful and perspectives career in tourism results in training a new standard professional, a specialist of many-sided knowledge,with the ability to fulfil tasks concerning thinking over, making and realizing management decisions. In order to develop tourist Carpathian region, the Precarpathian National University named after V.Stefanyk educates future experts in such specialities as "Tourism" and "Hospitality Industry". Involving youth in social cultural values and ideals, education contributes to maintaining social order and by providing realization of new technologies, scientific rethinking of existing knowledge education promotes social changes, society development, i.e. education operates as an agent of moral regulation facilitating social integration. Different interpretations of the concept «culture» were studied. The conclusion that culture is a multiaspect and multifunctional notion was made. Cultorological approach in education provides effectiveness of the process of putting culture as a social phenomenon into action. The fact of culturological direction extending of the whole educational process in the university interrelating to its components (common-cultural, professional and functional) is of great importance. Cultorological approach introduction to the process of training of the future tourism experts that is aimed at the developing of civil society values and an independent creative personality is a premise of modernization of higher education in Ukraine